1){2x +3y= 2{-2x + 5y = - 182x + 3y - 2x + 5y = 2 + (-18)8y = -16y = -16/8y = - 22x + 3*(-2) = 22x - 6 =22x = 2 + 62x = 8x= 8/2x = 4ответ: (4 ; -2)2) { x+ 4y = 39{2x - y = 15 |*4{x + 4y = 39{8x - 4y = 60x+4y +8x -4y = 39+609x = 99x= 1111 + 4y = 394y = 39 - 11y = 28/4y = 7ответ: (11 ; 7) №2.1){7x+2y = 9{5x + 2y = 11 |*(-1){7x +2y = 9{ - 5x - 2y = -117x + 2y - 5x - 2y = 9 - 112x = -2x = -17*(-1) + 2y = 92y = 9 +72y = 16y = 8ответ: (-1 ; 8)2) { 9x - 2y =-17 |*(-1){ x - 2y = 7{ - 9x + 2y = 17{ x - 2y = 7- 9x +2y +x - 2y = 17 + 7-8x= 24x = 24 / (-8)x= 33 - 2y = 7-2y = 7-3-2y = 4y = 4/(-2)y = -2ответ: (3 ; - 2)3){x + 7y = 19{ x + 5y = 13 | *(-1){ x +7y = 19{ -x - 5y = -13x + 7y - x - 5y = 19 - 132y = 6y = 3x + 7*3 = 19x + 21 = 19x = 19 - 21x= -2ответ : ( -2 ; 3).4) {5х - 2у = 15{2x - y = 7 |*(-2){5x -2y =15{ -4x +2y = -145x -2y -4x +2y = 15-14x = 15*1 - 2y = 15-2y = 15-5-2y = 10y = -5ответ : ( 1 ; -5).